Beyond Chinese Capitalism: Re-Conceptualising Notions of Chinese-ness in a Southeast Asian Business cum Societal Context - Michael Jacobsen (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2006)
This paper explores the role of the Chinese in a Southeast Asian business cum societal context; from different approaches towards Chinese-ness over different notions of intra- and inter-ethnic relation ending up with a critique of the idea of a Chinese diaspora in a Southeast Asian context. The paper furthermore argues that a culturalist reading of Southeast Asian Chinese modes of engaging in capitalist practices and societal entrenchments constitute a deception that produces a variety of stereotypes of Chinese-ness thus disregarding the complexity and dynamic developments within the ethnic Chinese community region-wise. Finally, in relation to Chinese business practices in a Southeast Asian context the paper suggests that cultural notions of guanxi and xinyong do not form a basis for doing business the Chinese way, only options, that intra-ethnic relations do not play an important role in transnational Chinese linkages, and that contemporary conceptions of Chinese identity are always negotiated with the dominant 'other' so as to secure the construction of an economic 'room' or space from where business can be conducted in an overall societal acceptable manner. Key words: Ethnic Chinese, diaspora, entrepreneurship, ethnicity, identity
hdl:10398/7408
Keywords: 330